A numerical scheme of coupling of fluid flow with three-dimensional fracture propagation. (September 2019) - Shen, Baotang; Shi, Jingyu
Abstract: In this paper, we combine a displacement discontinuity method (DDM) for rock deformation and a finite volume method (FVM) for fluid flow in fractures in rock mass to set up a numerical simulation scheme for coupling of hydraulic fracture flow with three-dimensional fracture propagation. Both the DDM and FVM discretise the fractures as the problem domain into small planar parts and same discretisation mesh is used by the two methods. The fluid flow is modelled with the cubic law in each control volume. A sequential coupling iteration procedure is employed to solve the two systems of linear equations. The numerical simulation scheme has been implemented in an existing three-dimensional fracture propagation code FRACOD 3D . Both the DDM and FVM have been verified previously by the authors and the sequential iteration procedure is tested in this paper. Then the numerical simulation scheme is employed to simulate an illustration example of hydraulic fracturing and investigate the effects of fractures' sizes and positions on the fracture propagation configurations.